Android Teledermatology Application for Skin Lesions Classification Based on Dermoscopic Images - Gymnastiar, Faris; Ismono, Yoyok Heru Prasetyo; Yulianto, Ahmad Wilda (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Skin cancer is a commonly diagnosed cancer worldwide, which is ranked third in Indonesia. While this type of cancer is curable in the early stage, there is an increase in the risk of death in the late stage. Thus, early detection is essential to minimize the spread of cancer. A prototype of an Android-based application was developed in this research to classify skin lesions. Dermoscopy images from the MNIST HAM10000 dataset comprised 10,015 images across seven skin cancer classes. Five pre-trained models from Keras, ResNet50V2, DenseNet121, InceptionV3, Xception, and MobileNet will be utilized for training and testing. During training, each model will be tested for classification performance based on changes in several hyperparameter variables, including learning rate, optimizer, batch size, and dropout.After testing, each model's performance improvement was obtained with adjustments to the training hyperparameters. The Xception model achieved the best accuracy at 92.5 percent. This model was then implemented in an Android-based application. The testing results on Android showed the same accuracy for original dermoscopic images from the test dataset. However, a decrease in accuracy was observed when testing with the camera, which noise or differences in resolution might cause